INCIDENCE OF MALARIA-TYPHOID CO-INFECTION AMONG PATIENTS ATTENDING GOMBE STATE UNIVERSITY CLINIC - ADAMU M.T.; GARBA L.; SINTALI A.; PUMA H.U. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Malaria is one of the febrile illness and the most common fatal disease in the world caused by one or more species of plasmodium parasites. Both malaria and typhoid fever remain the disease of major public health importance and cause of morbidity and mortality in tropical Africa.. This study aimed to determine the incidence of Malaria and Typhoid fever co-infection amongst patients attending Gombe State University Clinic. Five milliliter of venous blood samples were collected from five hundred (500) febrile patients within the age group of 1-70 years old.The results obtained showed an overall incidences of malaria, typhoid and co-infection of 440(88%), 380(76%) and 380 (76%), respectively. Gender-based incidence confirmed higher co-infection in male with 200(80%) cases compared to female with 180 (72%) cases. In terms of age group, coinfection was higher amongst patients within the ages of 21-30 years with 60.5% followed by those in the age group of 11-20 years with 21.1%. In conclusion, high prevalence of malariatyphoid fever co-infection was found amongst the febrile patients by this study.